Perlindungan Hukum Notaris Dalam Melaksanakan Rahasia Jabatan: notaris, rahasia jabatan - Aman Aman (Recital Review, 2019)
This is a research study that examines the legal protection for a notary in carrying out professional secrecy. Issues raised in this study discusses about how the forms of legal protection for a notary who beriktikat well in carrying out official secret and what is the rationale for the need for legal protection for well-meaning notary in carrying out professional secrecy. This study uses normative measures description, systematization and explanation of the content of positive law in depth by using a concept, approach to law and systematic analysis of synchronization. This study aims to assess and analyze in depth the forms of legal protection for a notary in carrying out official secret sebagaiamana stipulated in the Law on the post of notary as well as what is the rationale for the necessity of legal protection for a notary in carrying out professional secrecy. The results showed that the notary as a public official, is one of the professional positions that have a very large role in accommodating community legal act performed in accordance with the demands of the times. Authority and obligations of the notary given country through almost covers all the space for legal relations that exist in society, all social organizations both associations and foundations are legal entities require notary products in the establishment. To the notary in performing official secret protection needs, a form of protection is defined in the provisions of the legislation. The provisions of Article 66 is not to put the position of the notary as a public official in performing his remains protected, by the procedures of calling on concerned should be clearly, to avoid all the provisions in force, because the Notary is always bound to secrecy of office is always maintained. In addition, to protect the notary protocol in which includes letters dilekatkankan on minuta (original) deed and notaries are obliged to always keep up with sebaikbaiknya, because later declared the state archives. Notary as a public official authorized to make authentic act of all deeds, agreements, and provisions required by legislation and or desired by the stakeholders to be declared in an authentic deed, by guaranteeing date of deed, saving certificates, giving grosse, copies and official copies, all of it along permbuatan deeds were not also be assigned or excluded to other officials or those specified by law. The existence of as a supervisory agency referred to in Article 66 paragraph (1) to maintain balance and liabilities, in which the right of refusal held by notaries and law enforcement process is part to protect confidentiality. It therefore needed to provide legal protection.